HUBUNGAN GAYA PENGASUHAN AUTORITATIF DENGAN NUMBER SENSE PADA SISWA SD - Hildea Wenny Astria Fitri; Duryati Duryati (Universitas Negeri Padang, 2019)
Relationship between authoritative parenting style and number sense in elementary students. This study aims to see the relationship of authoritative parenting style with number sense in elementary students. The design of this study is a correlational quantitative method. The population in this study were elementary school students in Bukittinggi. The number of samples is 97 students of fifth grade elementary school in Bukittinggi. Subject collection using cluster sampling technique. Data was collected using an authoritative parenting style scale and number sense test. Data analysis techniques were processed using the product moment from Karl Pearson with the help of the SPSS version 16.0 program. The correlation coefficient is obtained at r = 0.298 and p = 0.008 (p <0.05). These results indicate that the hypothesis is accepted, which means there is a significant positive relationship between authoritative parenting style and student's number sense. Hubungan gaya pengasuhan autoritatif dengan number sense pada siswa SD. Penelitian ini bertujuan untuk melihat hubungan gaya pengasuhan autoritatif dengan number sense pada siswa SD. Desain penelitian ini adalah metode kuantitatif korelasional. Populasi dalam penelitian ini adalah siswa-siswiSDdi Bukittinggi. Jumlah sampel sebanyak 97 siswa kelas V SD di Bukittinggi. Pengambilan subjek menggunakan teknik cluster sampling. Data dikumpulkan dengan menggunakan skala gaya pengasuhan otoritatif dan tes number sense. Teknik analisis data diolah menggunakan product moment dari Karl Pearson dengan bantuan program SPSS versi16.0. Nilai koefisien korelasi didapat sebesar r = 0,298 dan p= 0,008 (p<0,05). Hasil tersebut menunjukkan bahwa hipotesis diterima, yang artinya terdapat hubungan yang positifsignifikan antara gaya pengasuhan otoritatif dengan number sense siswa.